Inspired by lipids (the Chevreul Award Lecture 2014). Issue 10 (11th August 2014) - Harwood, John L.
<x xml:space="preserve">Abstract</x> As an undergraduate student of Medical Biochemistry, I was unsure what I wanted to do with my life after graduating. Then, one day, I had a lecture about membrane lipids. It turned out that not only were they far from the inert structural compounds that they were often portrayed to be but they turned over quite rapidly. But there was one class of lipids—the higher inositides (PtdIns4P, PtdIns (4, 5) P2)—that had a T½ of only a few minutes! I found this fascinating and was inspired not only to do my post‐graduate work with J. N. (Tim) Hawthorne on inositides but to continue work on lipids ever since. I have no regrets for it has been a fascinating journey. The great French scientist Chevreul made contributions to several different areas of science so, in humble appreciation of his seminal discoveries, I will discuss some diverse lipid topics that I have worked on.